Islamic Analysis of Implementation of Zakat on Rice Agricultural Products in Improving Muzakki's Economic Welfare - Febria Sakinah; Luluk Fadliyanti (Experimental Student Experiences, 2024)
This study aims to determine the implementation of zakat on agricultural products and the welfare of farmers in Bungtiang Village, Sakra Barat District. This research is a qualitative approach. Data collection techniques in this study used observation, interviews and documentation. Determination of informants in this study using triangulation. The informants in this study consisted of 1 expert informant and 5 main informants and 2 additional informants. The results showed that from a study of the implementation of agricultural zakat, it was found that most people were aware of the obligation to issue agricultural zakat, but still channeled their zakat in a traditional consumptive manner, so that the amount of zakat issued was not in accordance with Islamic law, farmers only issued zakat as much as 10 % using either irrigation water or rainwater. From a study of the economic welfare of the community, it has been able to meet the needs of dharuriyyat (hifzu-dien, hifzun-nafs, hifzun-'Aql, hifzun-nasl and hifzun-maal) and hajiyyat.